2011
DOI: 10.1186/1475-2859-10-41
|View full text |Cite
|
Sign up to set email alerts
|

A novel family VII esterase with industrial potential from compost metagenomic library

Abstract: BackgroundAmong the vast microbial genomic resources now available, most microbes are unculturable in the laboratory. A culture-independent metagenomic approach is a novel technique that circumvents this culture limitation. For the screening of novel lipolytic enzymes, a metagenomic library was constructed from compost, and the clone of estCS2 was selected for lipolytic properties on a tributyrin-containing medium.ResultsThe estCS2 sequence encodes a protein of 570 amino acid residues, with a predicted molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 30 publications
2
39
1
Order By: Relevance
“…For example, the activity of the EstA esterase from Arthrobacter nitroguajacolicus was slightly stimulated (10-20 %) by the addition of DMSO (30 %) or acetonitrile (30 %), whereas lower concentrations (10 %) of these solvents reduced (20 to 90 %) the activity of esterases from Sulfolobus solfataricus (EST1) and Archaeoglobus fulgidus (Est-AF) (Kim et al 2008;Schutte and Fetzner 2007;Sehgal et al 2002). Similarly, several metagenomic esterases have been reported to be inhibited, unaffected or stimulated by the addition of DMSO (10-30 %), whereas all these enzymes were sensitive to acetonitrile and detergents (Triton X-100 and Tween-20) (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011). Since the metagenomic enzymes cannot be protected from the effect of low temperatures, the evolution of cold-adapted enzymes is the main mechanism of cold resistance in marine microbes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, the activity of the EstA esterase from Arthrobacter nitroguajacolicus was slightly stimulated (10-20 %) by the addition of DMSO (30 %) or acetonitrile (30 %), whereas lower concentrations (10 %) of these solvents reduced (20 to 90 %) the activity of esterases from Sulfolobus solfataricus (EST1) and Archaeoglobus fulgidus (Est-AF) (Kim et al 2008;Schutte and Fetzner 2007;Sehgal et al 2002). Similarly, several metagenomic esterases have been reported to be inhibited, unaffected or stimulated by the addition of DMSO (10-30 %), whereas all these enzymes were sensitive to acetonitrile and detergents (Triton X-100 and Tween-20) (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011). Since the metagenomic enzymes cannot be protected from the effect of low temperatures, the evolution of cold-adapted enzymes is the main mechanism of cold resistance in marine microbes.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that purified microbial and metagenomic esterases exhibit different sensitivities to organic solvents and detergents (Elend et al 2006;Fu et al 2011;Jiang et al 2012;Kang et al 2011). For example, the activity of the EstA esterase from Arthrobacter nitroguajacolicus was slightly stimulated (10-20 %) by the addition of DMSO (30 %) or acetonitrile (30 %), whereas lower concentrations (10 %) of these solvents reduced (20 to 90 %) the activity of esterases from Sulfolobus solfataricus (EST1) and Archaeoglobus fulgidus (Est-AF) (Kim et al 2008;Schutte and Fetzner 2007;Sehgal et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The units at the bottom of the tree indicate the number of substitution events. Reproduced with permission from figure 1b in Kang et al (2011). acylglycerols (Ellaiah et al 2004;Bornscheuer 2002;Litthauer et al 2002;Verger 1997;Ollis et al 1992).…”
Section: Lipasesmentioning
confidence: 99%
“…Multiple sequence alignment of Fae6 with a recently published metagemomic derived esterase (25) from family VII and the other related sequence from the BLASTp hits showed that the following residues were highly conserved: Ser253 within the G-E-S-A-G sequence motif, as well as the C-terminus located Glu307 and His507 ( Fig. S1; Supplementary material).…”
Section: Primary Structure Analysismentioning
confidence: 99%
“…The classical examples include esterase from Arthrobacter oxydans which is active against phenylcarbamate herbicides (32), a Bacillus subtilis esterase which hydrolyses p-nitrobenzyl esters (33) and a compost metagenome derived esterase, which in addition to hydrolyzing polyurethane and tertiary alcohol esters, also shows enantioselectivity against (R/S)-ketoprofen ethyl ester (25). Thus esterases belonging to family VII constitute one of the most versatile lipolytic enzyme groups.…”
Section: -O-[5-o-trans-feruloyl)-β-l-arabinofuranosyl]-d-xylopyranosementioning
confidence: 99%